The Social-Pedagogical Need to Improve the Skills of Physical Education and Sports Science Teachers - Mixeeva Aleksandra Ivanovna (Periodica Journal, 2023)
This article analyzes the prospects for future qualitative organization of physical education classes and its pedagogical necessity by enhancing the professional culture of future physical education teachers. The article is also based on the modern pedagogical methods, tools, available opportunities and the need for further improvement of the organization of physical education classes.
Keywords: Education system; physical education; physical culture; aesthetic education